London calling Gaza: The role of international collaborations in the globalisation of postgraduate burn care education - Evgenia Theodorakopoulou; Ioannis Goutos; Katrina Mason; Ali M Ghanem; Simon Myers (SAGE Publishing, 2019)
Burn injuries represent a significant epidemiological problem, with the vast majority occurring in low- to middle-income countries. These regions also represent areas where lack of socioeconomic growth and geopolitical instability pose additional barriers not only to healthcare provision but also to the acquisition of continuing professional development. Long-distance, web-based learning programmes ('tele-education') have been identified as a successful and powerful means of propagating up-to-date medical education and training in poor-resource, isolated or conflict-ridden regions. This report evaluates the role of tele-education in delivering a distance-learning Master's degree in Burn Care to a group of 11 healthcare professionals working in the occupied Palestinian territories (OPT), which was funded as part of a collaboration between Queen Mary University of London and IMET-Pal (International Medical Education Trust - Palestine). We present our experience in delivering the programme in a conflict-ridden part of the world, which includes the specific adaptations to tailor the programme to regional needs as well the unique challenges faced by students and faculty in enhancing the educational value of this unique initiative. The academic achievements of this group of healthcare professionals were found to be comparable to historical student cohorts from privileged socioeconomic backgrounds and the majority of students felt that participation in the programme contributed to a direct improvement to their daily burn care practices. The successful outcomes achieved by our students support the constantly emerging evidence that targeted, well-delivered, long-distance learning programmes can become powerful tools in combating inequalities in global healthcare and health education.